2018
DOI: 10.3136/fstr.24.591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion, Steam Explosion and Enzymatic Hydrolysis on Functional Properties of Wheat Bran

Abstract: This work evaluated the extrusion, steam explosion and enzymatic hydrolysis on the physical and chemical properties of wheat bran. At the same particle size, the three treatments effectively improve the water holding capacity and swelling capacity of wheat bran. Among them, steam exploded wheat bran had the highest water holding capacity and swelling capacity, followed by extruded wheat bran. All the three treatment have a weakened effect on sodium cholate adsorption capacity, cation exchange capacity and phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
6
11
1
Order By: Relevance
“…The increasing WAI of RPC blends can be attributed to the solubilization of insoluble dietary fiber by thermomechanical treatment. A high water binding capacity for extruded fiber-rich biopolymers was also reported in previous studies of lupin fiber [ 45 ], wheat bran [ 59 ], orange pomace [ 60 ], carrot residues [ 61 ] and barley meal [ 62 ]. Fetzer et al [ 63 ] reported cellulose, hemicellulose and lignin contents of 6.8 ± 0.6, 3.9 ± 0.6 and 11.4 ± 0.1 g/100 g d.m., respectively, for cold-pressed RPC.…”
Section: Discussionsupporting
confidence: 74%
“…The increasing WAI of RPC blends can be attributed to the solubilization of insoluble dietary fiber by thermomechanical treatment. A high water binding capacity for extruded fiber-rich biopolymers was also reported in previous studies of lupin fiber [ 45 ], wheat bran [ 59 ], orange pomace [ 60 ], carrot residues [ 61 ] and barley meal [ 62 ]. Fetzer et al [ 63 ] reported cellulose, hemicellulose and lignin contents of 6.8 ± 0.6, 3.9 ± 0.6 and 11.4 ± 0.1 g/100 g d.m., respectively, for cold-pressed RPC.…”
Section: Discussionsupporting
confidence: 74%
“…Wu et al. (2018) reported lightness, redness, blueness in wheat bran is 66.60, 7.17, and 2.20, respectively, supporting the present study. Laukova et al.…”
Section: Resultssupporting
confidence: 90%
“…The WSI of W was the best, reaching 19.55 g/100 g. After extrusion, the WHC of the different particle sizes of bran significantly decreased, whereas the WSI significantly increased (p < .05). WJ had the highest WSI, reaching 23.08 g/100 g. This result was similar to that reported by Zhong et al (2018) but in contrast to that by Wu et al (2018).…”
Section: Physical Property Analysissupporting
confidence: 88%
“…(2018) but in contrast to that by Wu et al. (2018). Several reasons may be proposed to account for this discrepancy.…”
Section: Resultscontrasting
confidence: 56%